Manganese and Sulfur Reduction by Soil Fungi on Post-Coal Mining Areas at Kutai Kartanegara, East Kalimantan - Bayu Widhayasa; Sudrajat Sudrajat; Rusdiansyah Rusdiansyah (AGRORADIX : Jurnal Ilmu Pertanian, 2019)
At such levels, manganese and sulfur can damage ecosystems and water distribution systems and causes serious problems to surrounding water-soil bodies in the post-coal mining areas. Soil fungal has a positive contribution to the improvement of soil physical and chemical properties. This research aims to determine the population size and diversity of soil fungi related to the manganese and sulfur concentrations at various stages of reclamation in East Kalimantan. The numbers of soil fungi increased in the year after reclamation and then decreased after aging for nine years. Aspergillus, Penicillium, Cephalosporium, Gliocladium, Humicola, Trichoderma, and Paecilomyces, were among the fungi found colonizing in the soil of the reclamation areas. The numbers of soil fungi were found negatively correlated with manganese concentrations. A negative correlation found between the numbers of soil fungi and sulfur concentrations. The slightly higher number of soil fungi in the reclamation areas can be attributed to lower manganese and sulfur concentrations.